The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.18332/tpc/128414
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral changes after the SHS-awareness campaign conducted in Ukraine in 2019

Abstract: is an open access, peer-reviewed online journal that encompasses all aspects of tobacco use, prevention and cessation that can promote a tobacco free society. The aim of the journal is to foster, promote and disseminate research involving tobacco use, prevention, policy implementation at a regional, national or international level, disease development-progression related to tobacco use, tobacco use impact from the cellular to the international level and finally the treatment of tobacco attributable disease thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The 14 included papers, [23][24][25][26][27][28][29][30][31][32][33][34][35][36] reported 13 mass-media campaigns implemented between 2002 and 2019 in eight countries (Vietnam, China, U.S., England, Scotland, Indonesia, Bosnia and Herzegovina, and Ukraine). These studies [23][24][25][26][27][28][29][30][31][32][33][34][35][36] evaluated mass media campaigns using pre-and post-campaign surveys or semi-structured interviews, [23][24][25][26][27][28][29]34] ecological studies (e.g., hospital admissions, Quitline call volume data), [33,35] not clearly described, [30,31] or social media metrics data [32,36]. The grey literature search located 61 mass media campaigns [12,17, from 44 countries implemented between 2016 and 2022.…”
Section: Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…The 14 included papers, [23][24][25][26][27][28][29][30][31][32][33][34][35][36] reported 13 mass-media campaigns implemented between 2002 and 2019 in eight countries (Vietnam, China, U.S., England, Scotland, Indonesia, Bosnia and Herzegovina, and Ukraine). These studies [23][24][25][26][27][28][29][30][31][32][33][34][35][36] evaluated mass media campaigns using pre-and post-campaign surveys or semi-structured interviews, [23][24][25][26][27][28][29]34] ecological studies (e.g., hospital admissions, Quitline call volume data), [33,35] not clearly described, [30,31] or social media metrics data [32,36]. The grey literature search located 61 mass media campaigns [12,17, from 44 countries implemented between 2016 and 2022.…”
Section: Study Selectionmentioning
confidence: 99%
“…Of these campaigns, two campaigns [26,36] assessed viewer perceptions of smoke-free campaign messagingloss-framed (i.e., demonstrating the risks of SHS) versus gain-framed (i.e., demonstrating the benefits of smokefree environments) advertisements. A 2010 U.S. based campaign found that loss-framed advertisements had higher emotional impact than gained framed advertisements (68% vs. 58%, p < 0.001) but gain-framed advertisements were more likely to be recalled than loss-framed C, A, S Vietnam [28,40,55,82], China [29,56,94], UK [24,25,27,31,43,72,80], US [23,26,33,38,48], Indonesia [30,36], Bosnia and Herzegovina [32], Ukraine [34,59], United Arab Emirates [86], Cuba [90], Jordan [89], India [50,92], Japan [69,87], Qatar [91], Luxembourg [88], Nepal [93], New Zealand [51,62], Belarus [74], Hong Kong [77],…”
Section: Awareness Of Campaignmentioning
confidence: 99%
See 3 more Smart Citations